INTERPRETATION ISSUE OF THE PRINCIPAL PURPOSE TEST - Vita Apriliasari (Politeknik Keuangan Negara STAN, 2019)
The existence of tax treaties has raised a base erosion and profit shifting (BEPS) concern through the circumvention of the provisions of those treaties. Consequently, following the release of the BEPS Action 6 Final Report by the Organisation for Economic Co-operation and Development, the Principal Purpose Test (PPT) has been introduced as a general anti abuse rule (GAAR) for tax treaties. As a BEPS action minimum standard, the PPT clauses are considered sufficient to prevent tax treaty abuses. However, since there has been no sufficiently clear guidance to the PPT implementation, several interpretation issues seem to arise. This situation is likely to put uncertainties for both tax administrations and taxpayers. This article aims to provide a literature review of the PPT clauses interpretation so as to help them to further address such issues. The discussion focuses on 4 (four) main elements of the PPT, (1) the interpretation of the phrase “one of the principal purposes”; (2) the reasonableness element; (3) the object and purpose of the relevant treaty provision; and (4) the burden of proof of the PPT.